Comparison of Antimicrobial Effects of Three Different Mouthwashes - Ahmad HAERIAN-ARDAKANI; Mahsa REZAEI; Mohammadreza TALEBI- ARDAKANI; Nasrin KESHAVARZ-VALIAN; Reza AMID; Mansoor MEIMANDI; Azadeh ESMAILNEJAD; Azarnoosh ARIANKIA (Tehran University of Medical Sciences, 2015)
Background: This study investigated the in vitro and in vivo antibacterial effects of three mouthwashes on su-pragingival plaque microbiota. The three mouthwashes under study were 0.2% chlorhexidine (CHX), Listerine®, and Persica (PM). Water was used as negative control. Methods: Supragingival plaque samples were collected from 32 patients with gingivitis in the Dental School of Shahid Beheshti University of Medical Sciences in March 2014. Plaque samples were swabbed on agar plates and discs (previ-ously immersed in the three mouthwashes) were placed on the agar. The zone of bacterial inhibition (ZOI) was meas-ured after incubation for 24 hours. For the in vivo testing, the same plaque samples were inoculated on agar and the colony forming units (CFU) were counted. The patients were then instructed to use the mouthwashes (cases) and wa-ter (controls) for two weeks, after which plaque samples were again collected, inoculated and the CFUs were counted. Results: For the ZOI test, 0.2% CHX inhibited the growth of bacteria to an average diameter of 18.38 mm, while Listerine®, PM and water caused no inhibition of bacterial growth around the discs after 24 hours. The mean bacterial count after using 0.2% CHX for two weeks decreased by 23.13 CFU. This was followed by Listerine®, with a mean reduction of 19.75 CFU. PM resulted in 13.5 CFU decrease in the mean bacterial count, while water reduced the bac-terial count by only 1 CFU. Conclusion: 0.2% CHX inhibits bacterial growth considerably. All three mouthwashes can reduce total bacterial count after 2 weeks although with different mean bacterial count reduction.